2013
DOI: 10.1177/1091581813504226
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Statistical Model to Predict the Potential for Repeated Dose and Developmental Toxicity of Dermally Administered Crude Oil and Relation to Reproductive Toxicity

Abstract: Petroleum (commonly called crude oil) is a complex substance primarily composed of hydrocarbon constituents. Based on the results of previous toxicological studies as well as occupational experience, the principal acute toxicological hazards are those associated with exposure by inhalation to volatile hydrocarbon constituents and hydrogen sulfide, and chronic hazards are associated with inhalation exposure to benzene and dermal exposure to polycyclic aromatic compounds. The current assessment was an attempt to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…For example, ARC content of petroleum substances tested herein has been related to their dermal carcinogenic potential. 24, 25, 30 Thus, it may be not surprising that ARC while content may be less useful for chemical fingerprinting and empirical groupings of petroleum substances as compared to heteroatom-class distribution. This raises a question of whether heteroatom content of petroleum substances, in addition to being useful for classification and grouping, may be indicative of their potential toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ARC content of petroleum substances tested herein has been related to their dermal carcinogenic potential. 24, 25, 30 Thus, it may be not surprising that ARC while content may be less useful for chemical fingerprinting and empirical groupings of petroleum substances as compared to heteroatom-class distribution. This raises a question of whether heteroatom content of petroleum substances, in addition to being useful for classification and grouping, may be indicative of their potential toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were prepared using previously published extraction procedures for routine isolation of complex polycyclic aromatic compounds (PAC) in petroleum substances. 16,17 The DMSO extraction procedure used herein is designed to concentrate the ‘biologically active’ fraction ( i.e. , aromatics) of the refinery streams; the extracts obtained using this method are used routinely for safety testing ( e.g.…”
Section: Methodsmentioning
confidence: 99%
“…42,43 Using compositional modeling developed as part of the HPV program, the potential hazards of 46 additional crude oils were predicted. 44 The results showed that the lowest predicted effect levels were similar to the lowest effect levels of one of the previously tested crude oils. This supported the view that the existing data could be used as a reasonable worst case and that further testing to characterize the hazards of individual crude oils was unnecessary.…”
Section: Characterization Of Toxicological Hazards Of Petroleum Productsmentioning
confidence: 65%